An analytical nonlinear dynamic model for linear guide with carriage flexibility. (January 2023) - Xu, Mengtao; Zhang, Hongzhuang; Li, Changyou; Yao, Guo; Zhang, Yimin; Gao, Yang
Abstract: Accurate estimation of vibration characteristics of linear guide is imperative for sophisticated structural performance of linear motion equipment. It has been illustrated that flexible model considering carriage deformation is a more precise description of realistic system. However, few dynamic model of carriage flexibility is found for vibration analysis when complex external load is applied. This paper proposes an analytical model to analyze the nonlinear vibration behavior of flexible linear guide system under multidirectional harmonic excitations. The outward deformation of flexible carriage skirt region is calculated by the classical deformation formula of vertical loaded cantilever beam. A lumped dynamic model accounting for segmented restoring force is proposed by coupling the vertical, lateral and rolling displacement and outward deformation. Dynamic responses of rigid and flexible models are compared, and the condition that neglects carriage flexibility is obtained. Numerical simulation exhibits abundant and fascinating nonlinear phenomena when the effects of external excitation, preload and carriage weight are discussed. Additionally, excitation experiments are performed to verify the proposed model. The developed theoretical model is promising for structure optimization of linear guide. Highlights: An analytical dynamic model for flexible linear guide is established. Restoring force involving carriage outward and coupled deformation is proposed. Critical condition that can neglect carriage flexibility is discussed. A wide variety of different nonlinear vibration behaviors are exhibited.